2013
DOI: 10.1007/s10509-013-1386-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an external interaction mechanism in solving agegraphic dark energy problems

Abstract: Agegraphic dark energy(ADE) and New-ADE models have been introduced as two candidates for dark energy to explain the accelerated expansion phase of the Universe. In spite of a few suitable features of these models some studies have shown that there are several drawbacks in them. Therefore in this investigation a new version of ADE and New-ADE are studied which can improve such drawbacks which appear in the ordinary ADE and New-ADE scenario. In fact we consider an interacting model of scalar field with matter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…There are many studies on this topic such as [184][185][186][187][188][189][190][191][192], where the authors explain that there are two definitions for the Lagrangian of a perfect fluid as L (2) m = p, respectively. However, in our case, this degeneracy is broken due to the non-minimal interaction of the scalar field and matter, and therefore we follow the approach proposed in [192], where it is shown that only for L (2) m = p one has a geodesic motion for perfect fluids.…”
Section: )mentioning
confidence: 99%
“…There are many studies on this topic such as [184][185][186][187][188][189][190][191][192], where the authors explain that there are two definitions for the Lagrangian of a perfect fluid as L (2) m = p, respectively. However, in our case, this degeneracy is broken due to the non-minimal interaction of the scalar field and matter, and therefore we follow the approach proposed in [192], where it is shown that only for L (2) m = p one has a geodesic motion for perfect fluids.…”
Section: )mentioning
confidence: 99%
“…ordinary cosmic time, t. As mentioned in the introduction, the Lagrangian of the matter is considered to verify L = L (m) + L (de) , [52,54], where the subscript m denotes matter (cold dark matter and baryons) and de refers to dark energy. Then the conservation equations could be rewritten as…”
Section: Conservation and Field's Equations In An Effective Dark Enermentioning
confidence: 99%
“…Also it is notable, if we choose β = 0, that the model reduces to EoS constant models (for instance C DM) [54]. By substituting (36) in (30), the dimensionless Hubble parameter is obtained as follows:…”
Section: Deceleration Parametermentioning
confidence: 99%
“…Amongst such parameters one can mention scalar spectral index n s , tensor spectral index n T and the tensor-to-scalar ratio r. From Eqs. (41) and (42), ρ s can be attained as…”
Section: Chaotic Inflationmentioning
confidence: 99%